OPTIMIZING CHARCOAL PRODUCTION: A COMPARISON OF THREE WOOD SPECIES AND METHODS - Perera, GCE (Association of Indonesian Forestry and Environment Researchers and Technicians, 2024)
For sustainable forestry management and environmental protection, it is crucial to compare three wood types and processes in order to optimise charcoal production. The purpose of this study was to evaluate the viability of using diverse waste materials and carbonization techniques to produce wood charcoal. The upcountry wet zone and low-country dry zone regions of Sri Lanka provided the samples, which were each repeated ten times and came in three different sample sizes. To make charcoal, these samples were put through the barrel and pit processes. The results showed that the barrel method produced 28% charcoal instead of the 21% produced by the pit method, demonstrating its higher efficiency and cost-effectiveness. This improvement was ascribed to the barrel's enhanced ability to regulate airflow and temperature during pyrolysis. The study emphasizes the use of wood off-cuts and the barrel method to increase efficiency, save costs, and improve charcoal quality. It provides helpful advice for small charcoal producers.